Approximation of fixed points for enriched Bℽμ mapping using a new iterative algorithm in CAT(0) space - Goswami, N.; Pathak, D. (Bulletin of the Karaganda University, 2025)
In this paper, we define enriched Bℽμ mapping in CAT(0) space and derive some fixed point results for such mapping with the help of averaged mapping. Our results extend some existing results. A new iterative algorithm is developed in CAT(0) space to approximate the fixed point of enriched Bℽμ; mapping. ∆-convergence and strong convergence of this iterative algorithm for enriched Bℽμ mapping is proved.
Keywords: CAT(0) space; Bℽμ; mapping; averaged mapping; fixed point